Efektivitas Program Kebijakan Desa Prioritas Percepatan Penurunan Stunting Kabupaten Sidoarjo - Muharram, Fajar (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research aims to determine the effectiveness of priority village policy programs in accelerating stunting reduction in Sidoarjo Regency. Referring to Siagian's theory of effectiveness which includes the role of government as a stabilizer, innovator, modernizer and implementer, this research examines how these roles are implemented in the local context. The method used is qualitative with a descriptive approach. Data was obtained through literature studies which included policy documents, government reports and relevant scientific articles. The technique for determining informants was carried out purposively, by selecting informants who had relevant experience and knowledge regarding the implementation of stunting programs at the village level, namely the Sidoarjo District Health Service. The research results show that the government's role as a stabilizer is reflected in the political and social stability that supports the desires of these programs. As an innovator, the government has succeeded in introducing various new initiatives that improve the quality of children's nutrition and health. The role as a modernizer can be seen from efforts to modernize health and sanitation facilities, as well as educating the public. As implementer, the government shows high commitment by directly implementing various program interventions. This research concludes that a holistic approach that integrates these four government roles has shown significant effectiveness in reducing stunting rates in Sidoarjo Regency. From the series of programs and policies implemented in Sidoarjo Regency to accelerate stunting reduction, holistic effectiveness has been implemented through various program implementations. such as Stabilizers to expand the scope of interventions, Innovators to integrate cross-sector activities, and Modernizers to improve data and information management. As the implementer itself, Sidoarjo Regency also implements regulations and establishes a responsible team, stunting programs can produce a significant positive impact in preventing stunting.